(untitled) (Analysis in Theory and Applications, 2013)
Let L be the infinitesimal generator of an analytic semigroup on L^2(R^n) with Gaussian kernel bound, and let L^-α/2 be the fractional integrals of L for 0 < α < n. In this paper, we will obtain some boundedness properties of commutators [b,L^-α/2] on weighted Morrey spaces L^p,κ(w) when the symbol b belongs to BMO(R^n) or the homogeneous Lipschitz space.